Death in the narrative of Eusebius of Caesarea: interpretations about suffering in ’Ecclesiastical History’ - Medeiros, Edalaura Berny; Cerqueira, Fábio Vergara (Romanitas - Revista de Estudos Grecolatinos, 2014)
As in On the death of the Persecutors, written by Christian rhetorician Lactantius (240-320), the tragic end of the Emperors enemies of faith received special attention in the narrative of Eusebius of Caesarea (265-339), bishop who became known as the "church history father" for his work Ecclesiastical History. The similarity allows us to conclude that his record went beyond of the mere description, but had a cautionary character. We intend to demonstrate that, for the maintenance of the internal logic of his speech, Eusebius interpreted the torment, for the Christian and non-Christian, in a double bias.